Prior Mental Fatigue Impairs Marksmanship Decision Performance - Head, James; Tenan, Matthew S.; Tweedell, Andrew J.; LaFiandra, Michael E.; Morelli, Frank; Wilson, Kyle M.; Ortega, Samson V.; Helton, William S. (Frontiers in Physiology, 2017)
Purpose: Mental fatigue has been shown to impair subsequent physical performance in continuous and discontinuous exercise. However, its influence on subsequent fine-motor performance in an applied setting (e.g., marksmanship for trained soldiers) is relatively unknown. The purpose of this study was to investigate whether prior mental fatigue influences subsequent marksmanship performance as measured by shooting accuracy and judgement of soldiers in a live-fire scenario. Methods: Twenty trained infantry soldiers engaged targets after completing either a mental fatigue or control intervention in a repeated measure design. Heart rate variability and the NASA-TLX were used to gauge physiological and subjective effects of the interventions. Target hit proportion, projectile group accuracy and precision were used to measure marksmanship accuracy. Marksmanship accuracy was assessed by measuring bullet group accuracy (i.e., how close a group of shots are relative to center of mass) and bullet group precision (i.e., how close are each individual shot to each other). Additionally, marksmanship decision accuracy (correctly shooting vs. correctly withholding shot) when engaging targets was used to examine marksmanship performance. Results: Soldiers rated the mentally fatiguing task (59.88 ± 23.7) as having greater mental workload relative to the control intervention (31.29 ± 12.3, t(19) = 1.72, p < 0.001). Additionally, soldiers completing the mental fatigue intervention (96.04 ± = 37.1) also had lower time-domain (standard deviation of normal to normal R-R intervals) heart rate variability relative to the control (134.39 ± 47.4, t(18) = 3.59, p < 0.001). Projectile group accuracy and group precision failed to show differences between interventions (t(19) = .98, p = 0.34, t(19) = .18, p = 0.87, respectively). Marksmanship decision errors significantly increased after soldiers completed the mental fatigue intervention (48% ± 22.4) relative to the control intervention (M = 32% ± 79.9, t(19) = 4.39, p < 0.001). There was a significant negative correlation between shooting response time and errors of commission (r = -.61; p = .004) when preceded by the mental fatigue intervention, but not the control (r = -.31; p = 0.17). Conclusion: The mental fatigue intervention was successful in eliciting fatigue which was supported subjectively and objectively. Marksmanship judgement